Pelatihan Budidaya Karang Hias Pada Kelompok Nelayan Sebagai Mata Pencaharian Alternatif di Kabupaten Konawe - Rais, Mohammad; Amijaya Husen, Suharta; Hamka, Eddy (Amaliah: Jurnal Pengabdian Masyarakat, 2025)
oral reefs are one of the typical ecosystems of tropical coastal waters, which have a very important role both ecologically and economically. Ecologically, coral reefs become a place to live, breed and feed thousands of species of fish, animals and plants that live in the sea. It is estimated that more than 3,000 species of marine biota can be found in the coral reef ecosystem. Along with the increasing rate of growth and industrialization, the condition of coral reefs is in a worrying condition. Beach reclamation activities, fishing using bombs and potassium cyanide poisons, construction of ports, and taking rocks as construction materials have resulted in severe damage to the coral reef ecosystem. Efforts to rehabilitate coral reef ecosystems by restoring the function and role of shellfish need to be carried out. One effort to tackle the problem of damage to coral reef ecosystems and fisheries production and to find alternatives to reduce pressure on the destruction of fishery resources can be done with coral transplantation technology. Coral transplantation is an attempt to transplant or cut live coral to be planted in a place that is damaged. Coral transplants in addition to conservation can also be used as ornamental coral cultivation media. The target of this activity is fishermen and the village government in order to know the techniques of ornamental coral cultivation so that it can give birth to new types of businesses as alternative livelihoods. The method of implementation is socialization, FGD and training in ornamental coral cultivation techniques with the material of ornamental coral trade policy, cultivation table making techniques, techniques for collecting seeds in nature and ornamental coral cultivation techniques. The results of dedication show a good understanding for participants in ornamental coral cultivation techniques.